Landing a job, sinking a career? The trade-off between occupational downgrading and quick reemployment according to unemployed jobseekers' career stage and job prospects. (December 2017) - Buchs, Helen; Murphy, Emily; Buchmann, Marlis
Highlights: Involuntary occupational downgrading at reemployment after unemployment. Trade-off between quality and speed of reemployment in an occupational labor market. Impact of relative availability of best fit vacancies (job prospects) on trade-off. Importance of job prospects for job search subject to career stage. Joint impact of composition of labor demand and career stage on trade-off. Abstract: A critical aspect of individual careers is the quality of jobs the unemployed match to at reemployment. The present study examines a trade-off the unemployed face in occupationally segmented labor markets: quickly exiting unemployment via downgraded reemployment or holding out for a skill adequate job while remaining unemployed. We analyze how the likelihood of involuntary status downgrading relates to the relative availability of 'best fit' vacancies at particular stages of a career. This study thus contributes to the broader literature on scar effects incurred from the experience of unemployment. Another contribution is the construction of refined measures of accessible vacancies at the micro level. Proportional hazard rate models are estimated using an inflow sample (2006–2014) of unemployed men with vocational education in Switzerland. Our results show that a higher relative availability of 'best fit' vacancies lowers jobseekers' risk of taking up a lower prestige job than the one sought. Career stage also matters for the trade-off between the quality and speed of reemployment, with trial stage unemployed being most responsive to job prospects.